2009
DOI: 10.1103/physreve.80.036115
|View full text |Cite
|
Sign up to set email alerts
|

Community detection in networks with positive and negative links

Abstract: Detecting communities in complex networks accurately is a prime challenge, preceding further analyses of network characteristics and dynamics. Until now, community detection took into account only positively valued links, while many actual networks also feature negative links. We extend an existing Potts model to incorporate negative links as well, resulting in a method similar to the clustering of signed graphs, as dealt with in social balance theory, but more general. To illustrate our method, we applied it … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
308
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 377 publications
(313 citation statements)
references
References 37 publications
3
308
0
2
Order By: Relevance
“…Leskovec et al [155] proposed a method to predict the signs of links (positive or negative), yet the prediction of both the existence of a link and its sign has not been well studied. Recent development of social balance theory may provide useful hints [156,157,158].…”
Section: Discussionmentioning
confidence: 99%
“…Leskovec et al [155] proposed a method to predict the signs of links (positive or negative), yet the prediction of both the existence of a link and its sign has not been well studied. Recent development of social balance theory may provide useful hints [156,157,158].…”
Section: Discussionmentioning
confidence: 99%
“…Social balance theory has also been confronted with large-scale data [5,6], and alternative theories for the interaction of positive/negative relations have also been proposed [6,11]. Focusing on link properties has also been emphasized in the problem of community detection in complex networks [12][13][14][15][16]. This opposes the traditional view of identifying network communities with a set of nodes [17], and it makes it possible for an individual to be assigned to different communities.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies on community partition in social networks with negative (or negatively weighted) edges (Yang et al, 2007;Bansal and Chawla, 2002;Demaine and Immorlica, 2003;Traag and Bruggeman, 2009). Bansal and Chawla (2002) introduced correlation clustering motivated by document clustering and agnostic learning and showed that it is an NP-hard problem to make a partition to a complete signed graph.…”
Section: Related Workmentioning
confidence: 99%
“…Demaine and Immorlica (2003) gave an approximation algorithm based on a linear-programming rounding and the region-growing technique and showed that the problem is APX-hard, i.e., any approximation would require improving the best approximation algorithms known for minimum multi-cut. Traag and Bruggeman (2009) adapted the concept of modularity to detect communities in networks where both positive and negative links are present and also evaluated the social network of international disputes and alliances. However, the algorithm involves several parameters that are hard to configure in practice.…”
Section: Related Workmentioning
confidence: 99%